1995
DOI: 10.1073/pnas.92.12.5356
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase beta bypasses in vitro a single d(GpG)-cisplatin adduct placed on codon 13 of the HRAS gene.

Abstract: We have examined the capacity of calf thymus DNA polymerases a, f, 6, and e to perform in vitro translesion synthesis on a substrate containing a single d(GpG)-cisplatin adduct placed on codon 13 of the human HRAS gene. We found that DNA synthesis catalyzed by DNA polymerases ca, 6, and E was blocked at the base preceding the lesion Among the possible mechanisms of mutagenesis is error-prone replication by cellular DNA polymerases past a DNA lesion followed by fixation of the mutation during subsequent rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 33 publications
(38 reference statements)
9
108
3
Order By: Relevance
“…Our laboratory (Canitrot et al, 1998;Ho mann et al, 1995) and other groups (Vaisman and Chaney, 2000;Vaisman et al, 1999) have demonstrated the ability of one of the mammalian DNA polymerases, Pol b, to e ciently catalyze error-prone translesion synthesis in vitro across the major intrastrand cross-links at the N-7 positions of adjacent guanine bases. (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory (Canitrot et al, 1998;Ho mann et al, 1995) and other groups (Vaisman and Chaney, 2000;Vaisman et al, 1999) have demonstrated the ability of one of the mammalian DNA polymerases, Pol b, to e ciently catalyze error-prone translesion synthesis in vitro across the major intrastrand cross-links at the N-7 positions of adjacent guanine bases. (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…An additional mechanism of resistance may be the consequence of an increased capacity of the cell to tolerate platinum-DNA lesions. We (Canitrot et al, 1998;Ho mann et al, 1995) and others (Vaisman and Chaney, 2000;Vaisman et al, 1999) have shown that puri®ed Pol b has the potential to e ciently catalyze error-prone translesion synthesis in vitro across the major intra-strand crosslinks at the N-7 positions of adjacent guanine bases. This mechanism has been proposed to be the primary mechanism that caused decreased cisplatin sensitivity in a series of cell lines, especially in the human ovarian carcinoma 2008/C13*5.25 cells where enhanced translesion synthesis of platinum lesions, ranging from 2 ± 5-fold compared to sensitive cell lines, has been observed (Johnson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been reported to possess 5Ј-deoxyribose phosphodiesterase activity (19). In recent years, ␤-pol has been implicated in the repair of several lesions that are repaired by the BER pathway, among them G:T and G:U mismatches (13,14,20), abasic sites (21)(22)(23), adducts introduced by monofunctional alkylating agents (14,24), and in vitro bypass of a d(GpG)-cisplatin adduct (25). ␤-Pol also appears to function in some specialized cases of DNA replication (26 -30).…”
Section: Base Excision Repair (Ber)mentioning
confidence: 99%
“…According to the work [13], the UV illumination of a semiconductor photocatalyst activates the catalysis and accelerates establishing a redox environment in the aqueous solution. Semiconductors act as sensitizers for light induced redox processes due to their electronic structure, which is characterized by a filled valence band and an empty conduction band [14]. So, the photocatalytic process of photopolymerization was induced as a result of light absorption on the surface semiconductor nanoparticles.…”
Section: Discussion Resultsmentioning
confidence: 99%